The role of E-HRM practices on digital era - Polat Dede, Nurten (IGI Global, 2019)
The changes brought about by trends such as globalization, technological developments, and knowledgebased economy, and the speed of these changes are forcing the enterprises to create more innovative ways of doing business and business processes. This rapid change has also affected and altered human resources departments' way of business. In this chapter, the changes in human resources management functions and applications with the effect of technology during this time have been explained. In addition, the electronic human resources management process and its applications, which have been more important as a result of developed human resources technology, are examined and presented in this chapter.
Keywords: Business; Technology; Changes; E-HRM; Digital Era